Ingatan Yang Mencekam : Studi Antropologi Memori Tentang Konflik Di Padamarari Poso - Michelle Alfelnis EB; Tasrifin Tahara (Journal of Peace, Security and Democracy, 2026)
The Poso conflict has left a profound collective memory among communities in the affected villages, including Bancea (Padamarari). While previous studies have examined the dynamics of violence and peacebuilding in Poso, there remains a limited anthropological understanding of how social memory is constructed, transmitted, negotiated, and mobilized by local communities in their post-conflict everyday life. This study aims to explore how traumatic experiences and lived memories of the conflict are reconstructed by different social groups, and how these memories shape reconciliation practices, intergroup relations, and long-term social stability. This research employs a qualitative anthropological approach involving twelve key informants, including customary leaders, women survivors, youth, and village officials. Data were collected through semi-structured interviews, participant observation, and field documentation over one month of fieldwork. Thematic analysis was applied to identify memory patterns, meaning-making processes, and the social mechanisms that underpin the reproduction of collective memory. The findings reveal three main insights. First, the memory of violence remains deeply embedded in villagers’ narratives and forms part of the community’s collective identity. Second, “strategic forgetting” emerges as an adaptive strategy used by community members to maintain social harmony and avoid renewed tensions. Third, the cultural value of Sintuwu Maroso serves as a key reconciliation mechanism, enabling trust-building across groups and facilitating the restoration of social cohesion. This study contributes to the broader literature on memory and post-conflict anthropology in Indonesia by demonstrating that collective memory functions not only as a historical burden but also as a social resource for strengthening community-based reconciliation.